Marketing Sportsgirl - Russell, Geoff (Bendigo, Vic. : Video Education Australasia, 1992)
Summary: Looks at the marketing of one of Australion retailers, Sportsgirl. Through interviews, graphics and narration, it details the decision-making processes and marketing philosophy employed during a typical new season's clothing range release and promotion
DVD format
Keywords: Fashion merchandising -- Australia; Clothing trade -- Australia; Clothing and dress -- Marketing